Evaluasi Pelaksanaan Skrining Hipotiroid Kongenital di Rumah Sakit Mardi Waluyo Metro - Irene Sekarjati (Bulletin of Community Engagement, 2024)
Evaluation of the Implementation of Congenital Hypothyroid Screening at Mardi Waluyo Metro Hospital. Congenital hypothyroidism screening is an important step as an early detection of congenital hypothyroidism in newborn babies. This screening or screening test is carried out when the baby is 48 to 78 hours old in life. The purpose of this screening is to sort out babies who suffer from congenital abnormalities from all the babies examined. This research is qualitative research with a descriptive analytical approach. The object to be researched is the evaluation of the implementation of the Congenital Hypothyroid Screening (SHK) program at Mardi Waluyo Metro Hospital. This research method is qualitative with a descriptive analytical approach. The results of the study from 362 live births that were screened for congenital hypothyroidism were only around 0.18% of all babies born in hospitals.